Causal relationship between Interleukin-27 expression levels and osteoporosis: a bidirectional mendelian randomization study - Yun Xue; You Zhou; Chunyan Li; Jingshuang Zhang; Fei Liu; Rui Shi (BMC Musculoskeletal Disorders, 2024)
Abstract Background This study aimed to evaluate the causal relationship between Interleukin-27 (IL-27) and osteoporosis by bidirectional Mendelian randomization (MR) analysis. Methods Firstly, the genome-wide association study summary data of osteoporosis (finn-b-M13_OSTEOPOROSIS) and IL-27 levels (ebi-a-GCST90012017) were picked out from the Integrative Epidemiology Unit (IEU) OpenGWAS database. After filtrating instrumental variables (IVs), the bidirectional MR analysis between IL-27 levels and osteoporosis was performed by MR-Egger, Weighted median, Simple mode, Weighted mode, and Inverse variance weighted (IVW). Subsequently, the sensitivity analysis was adopted to evaluate the reliability of the MR results via the Heterogeneity, Horizontal pleiotropy test and Leave-One-Out (LOO) analysis. Finally, the enrichment analysis of genes corresponding to SNPs related to IL-27 levels derived from eQTLGen database was executed to explore in depth the biological function and regulatory mechanism of these genes on osteoporosis occurrence. Results The bidirectional MR results based on IVW method revealed that IL-27 level as a risk factor was causally related to osteoporosis (P = 0.004, odds ratio (OR) = 1.123, 95% confidence interval (CI) = 1.037–1.217), whereas osteoporosis was not in significant connection with IL-27 levels (P > 0.05). In regard to the sensitivity analysis for forward MR results, there was no heterogeneity and horizontal pleiotropy, and no SNPs relevant to IL-27 levels existed severe bias, suggesting the reliability of forward MR analysis. Furthermore, a total of 74 genes corresponding to 26 SNPs of IL-27 levels were obtained and were mainly involved in immune and inflammatory pathways including MyD88-dependent toll-like receptor signaling pathway, Toll-like receptor signaling pathway, cytosolic DNA-sensing pathway and so forth. Conclusions This study supported that IL-27 level as a risk factor was causally connected with osteoporosis and might regulate the disease occurrence and progression by means of immune and inflammatory mechanisms, which could provide important reference and evidence for further exploring the role of IL-27 in the development of osteoporosis.